2005
DOI: 10.1093/occmed/kqi010
|View full text |Cite
|
Sign up to set email alerts
|

Practising evidence-based occupational healthin workers' groups: how to prevent sickness absence caused by influenza

Abstract: The case study shows that, as for other clinicians, the occupational physician can use the EBM paradigm according to the PICO model as a tool for providing appropriate solutions for the group of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…the patient or population or problem being addressed, the intervention or exposure being considered, comparison intervention or exposure when relevant, and the outcome of intervention or exposure 24,25) . Originally the PICO was developed for clinical studies 24,26) ; however, it is now being used in other fields 27,28) . For non-intervention studies, researchers have suggested that the intervention component of the PICO should be replaced with the exposure component because the former is a planned procedure while the exposure is an unintentional occurrence 22) ; for example physiotherapists' unintended exposure to RF EMFs from therapeutic diathermy devices.…”
Section: Methodsmentioning
confidence: 99%
“…the patient or population or problem being addressed, the intervention or exposure being considered, comparison intervention or exposure when relevant, and the outcome of intervention or exposure 24,25) . Originally the PICO was developed for clinical studies 24,26) ; however, it is now being used in other fields 27,28) . For non-intervention studies, researchers have suggested that the intervention component of the PICO should be replaced with the exposure component because the former is a planned procedure while the exposure is an unintentional occurrence 22) ; for example physiotherapists' unintended exposure to RF EMFs from therapeutic diathermy devices.…”
Section: Methodsmentioning
confidence: 99%
“…Recent initiatives in the application of EBM in daily occupational health practice are promising and show that there is more field-relevant evidence available in e.g. Medline than is generally assumed by OPs [15][16][17][18] . Moreover, a cohort study and two controlled trials with occupational health guidelines on low back pain and mental health problems confirmed their favourable effect on sick leave and prevention of disability [19][20][21] .…”
Section: Original Articlementioning
confidence: 99%
“…Vaccination indeed is an effective instrument for reducing absence from work and interrupting the contagion chain between patients and HCW, who often continue to work despite the risk of transmitting influenza to sick people, more fragile and exposed to complications than average. 1 A systematic vaccination of the hospital employees is useful for a good management of resources, as proven by several studies;…”
Section: Introductionmentioning
confidence: 99%